Diagnosing Delirium in Older Hospitalized Adults with Dementia: Adapting the Confusion Assessment Method to International Classification of Diseases, Tenth Revision, Diagnostic Criteria - Thomas, Christine; Kreisel, Stefan H.; Oster, Peter; Driessen, Martin; Arolt, Volker; Inouye, Sharon K. (Journal of the American Geriatrics Society (JAGS), 2012)
Objectives To compare performance characteristics of the Confusion Assessment Method (CAM) algorithm for screening and delirium diagnosis with criteria for delirium from the International Classification of Diseases, Tenth Revision (ICD‐10) and Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM‐IV) in high‐risk individuals. Design Prospective cohort study. Setting Academic geriatric hospital. Participants One hundred two individuals aged 80 to 100 hospitalized for acute medical illness. Measurements Complete CAM instrument (nine items), scored using the four‐item CAM diagnostic algorithm. Criterion standard classification of delirium was rated independently according to expert consensus based on DSM‐IV and ICD‐10 criteria for delirium. Results In 79 hospitalized participants, the CAM performed well for delirium screening (delirium prevalence of 24% according to DSM‐IV and 14% according to ICD‐10). Of all CAM features, acute onset and fluctuating course are most important for diagnosis (area under the receiver operating characteristic curve (AUC) = 0.92 in DSM‐IV and 0.83 in ICD‐10). The CAM diagnostic algorithm had a sensitivity of 0.74, a specificity of 1.0, and an AUC of 0.88 compared with the DSM‐IV reference standard and a sensitivity of 0.82, a specificity of 0.91, and an AUC of 0.85 compared with the ICD‐10. Compared with the ICD‐10, adding psychomotor change to the CAM algorithm improved specificity to 97%, but sensitivity fell to 55% (AUC = 0.96). Applying psychomotor change sequentially only to the group that the CAM algorithm identified as having no delirium improved sensitivity to 91% with specificity of 85% (AUC = 0.95). Conclusion Although the CAM diagnostic algorithm performed well against a DSM‐IV reference standard, adding psychomotor change to the CAM algorithm improved specificity and diagnostic value against ICD‐10 criteria overall in older adults with dementia and improved sensitivity and screening performance when applied sequentially in CAM‐negative individuals.